31P NMR assessment of the phosvitin‐iron complex in mayonnaise. (21st December 2018) - Merkx, Donny W.H.; Delić, Faruk; Wierenga, Peter A.; Hennebelle, Marie; van Duynhoven, John P.M.
Abstract: Lipid oxidation is the main reason for the limited shelf life of mayonnaise. One of the main catalysts of this process is iron, which is introduced in its ferric (Fe(III)) form via phosvitin, an egg yolk phosphoprotein rich in phosphoserines. The binding of Fe(III) to phosvitin and its ability to establish a redox couple with Fe(II) is believed to determine the oxidation rate of unsaturated lipids. In this work, a 31 P NMR based method was developed to quantify loading of phosvitin with Fe(III) and its reductive release. Both features could be quantified in model phosvitin solutions by exploiting the paramagnetic broadening of 31 P NMR signal of phosphoserine residues by Fe(III). This method was then successfully applied to quantify the phosvitin‐Fe(III) loading in mayonnaise water phase by liquid NMR, whereas 31 P NMR MAS could only provide a qualitative measure. The 31 P NMR method showed a direct relation between loading of the Fe(III)‐phosvitin complex and lipid oxidation. Abstract : The limited shelf life of mayonnaise is determined by the high amount of iron, which is known to catalyse lipid oxidation. This iron is introduced in its ferric (Fe(III)) form via phosvitin, a protein that is abundant in egg yolk. In this work, a 31 P NMR based method was developed to quantify the Fe(III) loading of phosvitin. A relation between loading of the Fe(III)‐phosvitin complex and lipid oxidation was found.